THE DIRECTIONS OF CREATION AN EFFECTIVE SYSTEM OF ORGANIZATIONAL KNOWLEDGE MANAGEMENT - В. П. Дюков; І. В. Рибаков; Є. Т. Штока (Ринкова економіка: сучасна теорія і практика управління)
The article examines the processes of formation of the knowledge economy. The approaches to the content of the "knowledge economy" category have been analyzed. The characteristics and features of the knowledge economy have been identified. The processes of the formation of corporate knowledge in the self-learning organizations have been studied. The directions of further development of knowledge management in organizations have been suggested.